Insights into the Mechanism of Severe Mitral Regurgitation: RT-3D TEE Guided Management with Pathological Correlation - Senthil Anand; Naktal Hamoud; Jess Thompson; Rajesh Janardhanan (Case Reports in Cardiology)
Mitral valve perforation is an uncommon but important complication of infective endocarditis. We report a case of a 65-year-old man who was diagnosed to have infective endocarditis of his mitral valve. Through the course of his admission he had a rapid development of hemodynamic instability and pulmonary edema secondary to acutely worsening mitral regurgitation. While the TEE demonstrated an increase in the size of his bacterial vegetation, Real Time 3D TEE was ultimately the imaging modality through which the valve perforation was identified. Through this case report we discuss the advantages that RT-3D TEE has over traditional 2D TEE in the management of valve perforation.